2015
DOI: 10.1134/s1061933x15030126
|View full text |Cite
|
Sign up to set email alerts
|

An AOT reverse micelle in a medium of supercritical carbon dioxide

Abstract: Reverse micelles of Aerosol OT in the medium of supercritical carbon dioxide have been simu lated by the molecular dynamics method. For the first time, a micelle in ternary water-Aerosol OT-super critical CO 2 has been simulated by describing the surfactant and the supercritical liquid in terms of the coarse grained approach. It has been shown that the structural and energetic characteristics of the micelle are, with a good accuracy, described within the framework of simplified models.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…Inspired by above perspective, an origin idea is that whether we can use this function of C 8 Benz to connect two dumbbell-like RMs and further generate a long wormlike RM. Unfortunately, the wormlike RMs are not shown in both simulation ,, and experimental , studies. To design wormlike RMs, it is necessary to enhance the active of C 8 Benz in this self-assembly system.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Inspired by above perspective, an origin idea is that whether we can use this function of C 8 Benz to connect two dumbbell-like RMs and further generate a long wormlike RM. Unfortunately, the wormlike RMs are not shown in both simulation ,, and experimental , studies. To design wormlike RMs, it is necessary to enhance the active of C 8 Benz in this self-assembly system.…”
Section: Resultsmentioning
confidence: 99%
“…When the RMs present a rodlike or wormlike shape, they could effective thicken the scCO 2 fluid and thus improve the viscosity and solubility of scCO 2 . Drive by this issue of practical importance, numerous experimental and theoretical work has been devoted to find surfactants with an appropriate aggregation behavior and generating wormlike RMs.…”
Section: Introductionmentioning
confidence: 99%
“…Molecular simulation has recently been widely employed to evaluate the nanoscale interaction among molecules. Molecular dynamics simulations of the structural properties of various surfactants at the scCO 2 /water interface have shown that fluorinated surfactants can be used as stable cosolvents to disperse nanoparticles in scCO 2 and that the strong electron dipole of the carbon–fluorine bond can improve the CO 2 -philicity of the surfactant. , Stone et al studied the behavior of DiH8 and DiF8 surfactants at the water/CO 2 interface , and found that fluorinated surfactants (DiF8) typically have larger free volumes. According to our preliminary study, the functionalization of the surfactant tail is key to improving the CO 2 -philicity, and the vast majority of surfactants possess alkane chain segments.…”
Section: Introductionmentioning
confidence: 99%